Contributions of Mexican mathematicians abroad in pure and applied mathematics : second meeting, Matemáticos Mexicanos en el Mundo, December 15-19, 2014, Centro de Investigación en Matemáticas, Guanajuato, Mexico - Galaz-García, Fernando; Pardo, J. C.; Solórzano, Pedro, 1981- (Aportaciones matemáticas., 2018)
This volume contains the proceedings of the Second Workshop of Mexican Mathematicians Abroad (II Reunión de Matemáticos Mexicanos en el Mundo), held from December 15-19, 2014, at Centro de Investigación en Matemáticas (CIMAT) in Guanajuato, Mexico. This meeting was the second in a series of ongoing biannual meetings aimed at showcasing the research of Mexican mathematicians based outside of Mexico. The book features articles drawn from eight broad research areas: algebra, analysis, applied mathematics, combinatorics, dynamical systems, geometry, probability theory, and topology. Their topics r.